Sensitive Determination of Terazosin in Pharmaceutical Formulations and Biological Samples by Ionic-Liquid Microextraction Prior to Spectrofluorimetry - Mohsen Zeeb; Mahdi Sadeghi (International Journal of Analytical Chemistry)
An efficient and environmentally friendly sample preparation method based on the application of hydrophobic 1-Hexylpyridinium hexafluorophosphate [Hpy][PF6] ionic liquid (IL) as a microextraction solvent was proposed to preconcentrate terazosin. The performance of the microextraction method was improved by introducing a common ion of pyridinium IL into the sample solution. Due to the presence of the common ion, the solubility of IL significantly decreased. As a result, the phase separation successfully occurred even at high ionic strength, and the volume of the settled IL-phase was not influenced by variations in the ionic strength (up to 30% w/v). After preconcentration step, the enriched phase was introduced to the spectrofluorimeter for the determination of terazosin. The obtained results revealed that this system did not suffer from the limitations of that in conventional ionic-liquid microextraction. Under optimum experimental conditions, the proposed method provided a limit of detection (LOD) of 0.027 μg L−1 and a relative standard deviation (R.S.D.) of 2.4%. The present method was successfully applied to terazosin determination in actual pharmaceutical formulations and biological samples. Considering the large variety of ionic liquids, the proposed microextraction method earns many merits, and will present a wide application in the future.